Βιβλιοκρισία: L. BALLETTO, Aspetti e Momenti della Storia di Cipro (secc. XIII-XV) [Centre de Recherche Scient. Recueil de travaux IV], Λευκωσία 2018 - ΚΟΥΜΑΝΟΥΔΗ, Μαρινα (Byzantina Symmeikta, 2020)
Βιβλιοκρισία: L. Balletto, Aspetti e Momenti della Storia di Cipro (secc. XIII-XV) [Centre de Recherche Scientifique. Recueil de travaux IV], Λευκωσία 2018